2020
DOI: 10.1002/advs.202000991
|View full text |Cite
|
Sign up to set email alerts
|

Double Negative Differential Resistance Device Based on Hafnium Disulfide/Pentacene Hybrid Structure

Abstract: Recently, combinations of 2D van der Waals (2D vdW) materials and organic materials have attracted attention because they facilitate the formation of various heterojunctions with excellent interface quality owing to the absence of dangling bonds on their surface. In this work, a double negative differential resistance (D-NDR) characteristic of a hybrid 2D vdW/organic tunneling device consisting of a hafnium disulfide/pentacene heterojunction and a 3D pentacene resistor is reported. This D-NDR phenomenon is ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Most importantly, to achieve an effective physical tunneling barrier and/or momentum phase mismatch, typical tunneling devices require complex device architectures such as multiple heterojunctions, twisted homojunctions, and reconfigurable devices with multigate-based configurations. [13,[26][27][28][29] These complex device configurations not only limit the effective channel area but also cause undesired heterointerface defect states that obstruct the elucidation of the fundamental origin of the NDR behavior. [30,31] In particular, experimental evidence for NDR via band-to-band tunneling (BTBT) at V CNP in homogenous materials free of undesired heterointerface defect states has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, to achieve an effective physical tunneling barrier and/or momentum phase mismatch, typical tunneling devices require complex device architectures such as multiple heterojunctions, twisted homojunctions, and reconfigurable devices with multigate-based configurations. [13,[26][27][28][29] These complex device configurations not only limit the effective channel area but also cause undesired heterointerface defect states that obstruct the elucidation of the fundamental origin of the NDR behavior. [30,31] In particular, experimental evidence for NDR via band-to-band tunneling (BTBT) at V CNP in homogenous materials free of undesired heterointerface defect states has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Trajković and Willson [20] considered two-terminal circuits with N-type current-voltage characteristics using a special connection of two BJTs and three resistors. Jung et al [21] reported fabricating an N-type double-NDR device using a 3D hybrid structure that includes two 2D vdW/organic heterojunctions and one organic resistor. Kobashi et al [22] proposed a new NDR transistor based on a p-n heterojunction of organic semiconductors with well-balanced carrier transport through the junction.…”
Section: Reviewmentioning
confidence: 99%
“…Considerable attention is paid to developing new NDR devices [21][22][23][24][25][26][27][28]30,31,33,[36][37][38][39], indicating the research topic's relevance.…”
Section: Reviewmentioning
confidence: 99%
“…Second, the operating voltage of the NDR device must be reduced, which allows a low power consumption budget. Even though the reproducibility, uniformity, robustness, and operational voltage assurances mentioned above cannot be overemphasized, previous studies have suggested a possibility of a single I – V measurement test on a unit device. ,, Therefore, for practical application of NDR devices, it is highly necessary to realize NDR behavior stably even in large-area, large-scale, and multiple operation cycles with forward and reverse sweeps.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal dichalcogenides (TMDs) have been attracting significant attention for the fabrication of NDR devices owing to their desirable structure. The TMDs can form sharp interfaces with other materials through weak van der Waals (vdW) interactions, which enables high-quality heterostructures without a lattice mismatch and trap sites leading to device-to-device and cycle-to-cycle variations. ,,, Owing to the aforementioned merits of TMDs, novel applications on an atomic scale with high-quality heterostructure electronic devices (i.e., multivalued logic, photovoltaic devices, tunneling diodes, and neuromorphic devices) have been extensively developed. However, due to the technical limitations of adequate large-scale production of TMDs, properties determining the feasibility, such as device productivity and reliability, have not been investigated in previous studies …”
Section: Introductionmentioning
confidence: 99%